Prolungamento della vita, cure palliative e relazione medico-paziente: memoria di un dibattito precedente al fenomeno dell'eutanasia - Vestri, Gabriele (Lex Social: Revista de Derechos Sociales, 2024)
Questo lavoro cerca di approssimarsi a tre fenomeni base in materia di eutanasia: il prolungamento della vita, le cure palliative e la relazione medico paziente, coscienti delle obbligazioni del medico e sicuramente dei diritti del malato. ----------------------------------------------------------- This work attempts to define the three basic elements of the subject of euthanasia: Prolonging life, palliative care, and doctor patient relationships. These elements, dealt with on a daily basis, are obligatory and antecedent for talking about euthanasia. The first part of this work discusses the possibility of prolonging the life of a terminally ill patient in relationship to aggressive therapy. From this process, an attempt is made to find equilibrium between the disease’s process and the palliative care. We must consider that during the length of a disease, the relationship exists not only between the patient and his family but also the patient and doctor who is bound by medical obligations and patient’s rights.